mec Genes in Methicillin Resistant Staphylococcus aureus - Umami, Zahra; Warni, Asri Indahning; Wahyuni, Dewi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) manifests antibiotic resistance, especially for the β-lactams antibiotic group. MRSA bacteria are a common cause of infection in humans. The antibiotic resistance characteristic comes from the mecA, mecB, and mecC genes in the bacterial chromosome. mecA is the most common gene found in MRSA. Therefore, it is essential to know the role of the mecA gene in antibiotic resistance. This paper searched the literature about MRSA bacteria, the mec gene, and their relationship to cause resistance. The results showed that the mec gene found in MRSA bacteria causes antibiotic resistance in penicillin groups. Methicillin-resistant Staphylococcus aureus (MRSA) manifests antibiotic resistance, especially for the β-lactams antibiotic group. MRSA bacteria are a common cause of infection in humans. The antibiotic resistance characteristic comes from the mecA, mecB, and mecC genes in the bacterial chromosome. mecA is the most common gene found in MRSA. Therefore, it is essential to know the role of the mecA gene in antibiotic resistance. This paper searched literature about MRSA bacteria, the mec gene, and their relationship to cause resistance. The results showed that the mec gene found in MRSA bacteria causes antibiotic resistance in penicillin groups.